(untitled) (European Journal of Marketing and Economics, 2021)
The entrenched and firm conviction that man is master of nature while being separate from it has fostered the culture of the indiscriminate use of natural resources, the destruction of eco-systems and a waste society. Over recent decades, behind the urgent need to halt the ecological drift, the natural landscape has been of considerable interest in various disciplinary contexts including biology, from which it has gained renewed consideration from the “ecology of landscape” perspective, and ethics. Once the theoretical aspects of the ecology of the landscape concept have been clarified, I will demonstrate that the human condition is part of the natural environment. On this basis I will highlight the necessity for man to develop an ecological awareness founded on responsibility regarding biodiversity. The ethics of responsibility, enlightened by an ecological awareness, have to inspire living and guide environmental policy-making.